Komunikasi Publik Intelijen dalam Mendukung Pemanfaatan Energi Nuklir di Indonesia - Aanwijzi, Rizkyagi (Universitas Tribhuwana Tungga Dewi, 2024)
Nuclear energy is currently an option to be applied in many countries, because it is considered to be a solution to the growing need for electrical energy. the need for electrical energy is getting bigger. However, until now there are still various challenges or problems to realize its utilization in Indonesia. to realize its utilization in Indonesia. One of the challenges in the development of development of nuclear energy is that there are still wrong perceptions related to the use of nuclear energy. nuclear energy. This perception to a certain extent results in the rejection of some people towards nuclear power plants. there is a rejection of some people towards nuclear power plants (Pembangkit Listrik Tenaga Nuklir). Nuclear Power Plant). Based on Law No. 17/2011 on State Intelligence State Intelligence, BIN plays a role in detection and anticipation efforts that threaten national security and interests. and national interests. Therefore, this research aims to analyze the role of intelligence in supporting accurate public communication, transparent, and fact-based public communication related to the utilization of nuclear energy in Indonesia, and analyze the causes of miscommunication in the utilization of nuclear energy in Indonesia. Indonesia. Qualitative research was chosen as the research method due to complexity of the problems associated with the utilization of nuclear energy in Indonesia, such as public perception, technical challenges, and government policies. government. The results of this study found that the construction of nuclear power plants in Indonesia faces a number of obstacles, including the lack of political will and strong regulations. Despite having fulfilled most aspects of required infrastructure, NPP has not yet become a priority issue.Energi nuklir saat ini menjadi pilihan untuk diaplikasikan di banyak negara, sebab dianggap dapat menjadi solusi terhadap kebutuhan energi listrik yang semakin besar. Namun, hingga saat ini masih terdapat berbagai tantangan atau persoalan untuk mewujudkan pemanfaatannya di Indonesia. Salah satu tantangan pembangunan energi nuklir adalah masih adanya persepsi yang salah terkait dengan penggunaan energi nuklir. Persepsi tersebut pada batas tertentu berakibat pada masih terdapat penolakan sebagian masyarakat terhadap PLTN (Pembangkit Listrik Tenaga Nuklir). Berdasarkan Undang-Undang Nomor 17 Tahun 2011 tentang Intelijen Negara, BIN berperan dalam upaya deteksi dan antisipasi yang mengancam keamanan serta kepentingan nasional. Untuk itu penelitian ini bertujuan untuk menganalisis peran intelijen dalam mendukung komunikasi publik yang akurat, transparan, dan berbasis fakta terkait pemanfaatan energi nuklir di Indonesia, serta menganalisis penyebab miskomunikasi dalam pemanfaatan energi nuklir di Indonesia. Penelitian kualitatif dipilih sebagai metode penelitian karena kompleksitas masalah yang terkait dengan pemanfaatan energi nuklir di Indonesia, seperti persepsi masyarakat, tantangan teknis, dan kebijakan pemerintah. Adapun hasil dari penelitian ini menemukan, pembangunan PLTN di Indonesia menghadapi sejumlah kendala, termasuk kurangnya political will dan regulasi yang kuat. Meskipun telah memenuhi sebagian besar aspek infrastruktur yang diperlukan, PLTN belum menjadi isu prioritas.